2007
DOI: 10.1002/cyto.b.20395
|View full text |Cite
|
Sign up to set email alerts
|

CD158k/KIR3DL2 is a useful marker for identifying neoplastic T‐cells in Sézary syndrome by flow cytometry

Abstract: Enumeration of neoplastic T-cells in peripheral blood specimens is necessary for the diagnosis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 25 publications
3
48
0
1
Order By: Relevance
“…In normal individuals, expression of CD158k is highly restricted to a minor NK cell subset and rare CD3+ CD8+ circulating T lymphocytes [37]. On the other hand, in patients with SS, CD158k is highly expressed on circulating Sé zary cells [36,38,39]. Gene expression analysis has revealed that T-plastin (a member of a highly conserved cytoplasmic protein family), EphA4, the Ephreceptor subfamily of transmembrane protein-tyrosine kinases, and the transcription factor Twist, which functions as a regulator of mesodermal differentiation, are all aberrantly expressed on Sé zary cells [40,41].…”
Section: Sé Zary Cellsmentioning
confidence: 98%
“…In normal individuals, expression of CD158k is highly restricted to a minor NK cell subset and rare CD3+ CD8+ circulating T lymphocytes [37]. On the other hand, in patients with SS, CD158k is highly expressed on circulating Sé zary cells [36,38,39]. Gene expression analysis has revealed that T-plastin (a member of a highly conserved cytoplasmic protein family), EphA4, the Ephreceptor subfamily of transmembrane protein-tyrosine kinases, and the transcription factor Twist, which functions as a regulator of mesodermal differentiation, are all aberrantly expressed on Sé zary cells [40,41].…”
Section: Sé Zary Cellsmentioning
confidence: 98%
“…Loss of CD26 expression is also useful in the identification of Sezary cells, being observed in 50% of cases [135][136][137]. More recently, the aberrant expression of the MHC class I-binding, killer immunoglobulin-like receptor (KIR) CD158j, normally expressed by natural killer cells, was described in the majority of patients examined with SS [138,139]. Molecular studies, including detection of a clonal TCR gene rearrangement by PCR and the presence of a clonal cytogenetic abnormality, provide evidence of T-cell clonality.…”
mentioning
confidence: 99%
“…CD158k is expressed by tumor T cells of Sezary syndrome, advanced MF, and pc-ALCL. [171819202122] CD158k acts as an inhibitory coreceptor in Sezary cells given its ability to downmodulate CD3-dependent early signaling events. In addition, our data provide evidence for a possible role of KIR3DL2 in the maintenance of a high circulating malignant-cell burden by preventing activation-induced cell death.…”
Section: Iph4102 (Anti-cd158k Monoclonal Antibody)mentioning
confidence: 99%